Some Properties of* - Quasihyponormal Operators - Muraeh Atheab, Nidaa; Dawood Mohsen, Salim (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we introduce a new generalization for the hyponormal operator, which is *-quasihyponormal, and discuss some important theorems of this concept, as well as some properties of this operator that have been given following this work. Finally, this work gives another objective: solvability of some types of bounded linear operator called - -commuting operator equations when there is a *-quasihyponormal operator and finding the value  of these equations in a Hilbert space H.